Analisis Pengetahuan Keuangan Mahasiswa Akan Literasi Keuangan Di Program Studi Pendidikan Ekonomi : Studi Kasus Sebelum Masa Covid-19 - Parera, Helena Rosalia (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2023)
This research is an analysis of students' financial knowledge of financial literacy in the pre-covid-19 period. The research objective is to find out how well students understand financial literacy. Type of quantitative research with descriptive analysis research method. The results show that students' financial knowledge of financial literacy is in the low category of 58.9%. This is because this research was conducted in 2019 where the financial literacy movement has not been echoed for a long time, students do not understand what financial literacy is, how important financial knowledge must be mastered in order to be able to manage personal finances so that they can save for long-term investment or shop moderately based on needs not based on desires.